ChemInform Abstract: Manganese Ferrite Nanoparticle Catalyzed Tandem and Green Synthesis of Spirooxindoles. Issue 13 (March 2015) - Ghahremanzadeh, Ramin; Rashid, Zahra; Zarnani, Amir‐Hassan; Naeimi, Hossein
Abstract A novel one‐pot three‐component reaction of isatins, anilinolactones, and malonitrile furnishes spirooxindoles with potential biological activity.